Human adipose tissue-derived SSEA-4 subpopulation multi-differentiation potential towards the endothelial and osteogenic lineages - Mihaila, Silvia M. (2013)
Human adipose tissue has been recently recognized as a potential source of stem cells for regenerative medicine applications, including bone tissue engineering (TE). Despite the gathered knowledge regarding the differentiation potential of human adipose tissue-derived stem cells (hASCs), in what concerns the endothelial lineage many uncertainties are still present. The existence of a cell subpopulation within the human adipose tissue that expresses a SSEA-4 marker, usually associated to pluripotency, raises expectations on the differentiation capacity of these cells (SSEA-4+hASCs). In the present study, the endothelial and osteogenic differentiation potential of the SSEA-4+hASCs was analyzed, aiming at proposing a single-cell source/ subpopulation for the development of vascularized bone TE constructs. SSEA-4+hASCs were isolated using immunomagnetic sorting and cultured either in a-MEM, in EGM-2 MV (endothelial growth medium), or in osteogenic medium. SSEA-4 +hASCs cultured in EGM-2 MV formed endothelial cell-like colonies characterized by a cobblestone morphology and expression of CD31, CD34, CD105, and von Willebrand factor as determined by quantitative reverse transcriptase (RT)-polymerase chain reaction, immunofluorescence, and flow cytometry. The endothelial phenotype was also confirmed by their ability to incorporate acetylated lowdensity lipoprotein and to form capillary-like structures when seeded on Matrigel. SSEA-4 +hASCs cultured in a-MEM displayed fibroblastic-like morphology and exhibited a mesenchymal surface marker profile (>90% CD90+/CD73+/CD105+). After culture in osteogenic conditions, an overexpression of osteogenic-related markers (osteopontin and osteocalcin) was observed both at molecular and protein levels. Matrix mineralization detected by Alizarin Red staining confirmed SSEA-4 +hASCs osteogenic differentiation. Herein, we demonstrate that from a single-cell source, human adipose tissue, and by selecting the appropriate subpopulation it is possible to obtain microvascular-like endothelial cells and osteoblasts, the most relevant cell types for the creation of vascularized bone tissue-engineered constructs.